Specific Features of the Concept of ‘’Genre’’: Genres of Journalism through the Prism of the Functioning of Genres in Art and Literature (Comparative Analysis) - Eritsyan, Hasmik (Bulletin of Yerevan University B: Philology, 2024)
This research is devoted to the peculiarities of the functioning of genres in journalism. To understand the specifics of genre diversity and genre systems in journalistic activity, in the first part of our study, we have tried to characterize the concept of ’’genre’’ in general and have examined the features of the functioning of genres in art, in particular, in literature. In the second part of our study, we have studied the concept of ’’genre’’ and its characteristics in the context of journalistic activity, where we have identified a correlation between the specifics of the activity itself (its functions, alterations, and multilateralism of definitions), technological progress and the functioning of genres (formation, popularization, transformation, extinction, revival). The result of the comparative analysis is a table of the frequency of manifestation of the main genre characteristics in literary studies and journalism. So, through the description of genre characteristics and comparative analysis, we can better understand the specific features of the functioning of genres in journalism, including in modern multimedia journalism.